Decade of Healthy Aging 2020-2030: international and local arctic context - Golubeva, Elena; Soloviev, Andrey (Magyar Gerontológia, 2022)
Healthy aging has become an important policy issue at all levels of the society. The key international document is the World Health Organization’s (WHO) plan for a Decade of Healthy Ageing 2020–2030 which is the 2nd action plan of the WHO ‘s Global strategy on aging and health [1]. The Plan consists of 10 years of concerted, catalytic, sustained collaboration to improve the lives of older people, their families, and their communities. Older people themselves are at the core of this plan, and it brings together a variety of actors: governments, civil society, international agencies, professionals, media, and the private sector. The Plan also notes that healthy aging is not only a healthcare issue but also needs to engage many other sectors.